Prevalence of Antimicrobial Resistance and Virulence Gene Elements of Salmonella Serovars From Ready-to-Eat (RTE) Shrimps - Beshiru, Abeni; Igbinosa, Isoken H.; Igbinosa, Etinosa O. (Frontiers in Microbiology, 2019)
Gastrointestinal illnesses continue to be a global public health risk. Exposure to foodborne Salmonella directly or indirectly through consumption of ready-to-eat seafood can be an important route of infection to humans. This study was designed to estimate the population cell density, prevalence, virulence gene signatures and antibiotic resistance of Salmonella serovars from ready-to-eat shrimps. Ready-to-eat (RTE) shrimp samples were obtained from different open markets in Delta and Edo States, Nigeria from November 2016 to October 2017. We employed classical and polymerase chain reaction (PCR) approaches. The mean Salmonella species enumerated from the RTE shrimps ranged from -0.301 to 5.434 log10 cfu/g with 210/1440 (14.58%) of the RTE shrimp samples harboured Salmonella species. After biochemical and PCR approach, the identified isolates were Salmonella Enteritidis 11(24.4%), Salmonella Typhimurium 14(31.1%) and other Salmonella spp. 20(44.4%). All Salmonella species recovered were resistant to penicillin and erythromycin with 100% sensitivity to cefotaxime, cephalothin, colistin and polymyxin B. Findings on the multidrug-resistant (MDR) profile showed that a total of 9/14 (64.3%) of Salmonella Enteritidis were resistant to 5 antibiotics which belongs to 3 different groups of antimicrobials with a multiple antibiotic-resistant (MAR) index of 0.21; while 3/11 (27.3%) of Salmonella Typhimurium were resistant to 11 antibiotics which belongs to 7 different groups of antimicrobials with a MAR index of 0.46. Virulence genes (spiA, sipB, invA, sifA, fljB, and sefA) and resistance genes (class 1 and II integrase, sul2, catB3, flor, tmp, blaTEM, strB, dfr1, and tetC) were also detected in some of the Salmonella species with variable percentage. This study indicates that ready-to-eat shrimps are probable reservoirs harbouring Salmonella strains. The identified Salmonella isolates which exhibited virulence determinants and antibiotic-resistant coupled with high MAR index constitute a consumer health risk to the communities.